MiR‐199a‐3p and miR‐214‐3p improve the overall survival prediction of muscle‐invasive bladder cancer patients after radical cystectomy. (6th September 2017) - Ecke, Thorsten H.; Stier, Katja; Weickmann, Sabine; Zhao, Zhongwei; Buckendahl, Laura; Stephan, Carsten; Kilic, Ergin; Jung, Klaus
Abstract: To improve the clinical decision‐making regarding further treatment management and follow‐up scheduling for patients with muscle‐invasive bladder cancer (MIBC) after radical cystectomy (RC), a better prediction accuracy of prognosis for these patients is urgently needed. The objective of this study was to evaluate the validity of differentially expressed microRNAs (miRNAs) based on a previous study as prognostic markers for overall survival (OS) after RC in models combined with clinicopathological data. The expression of six miRNAs (miR‐100‐5p, miR‐130b‐3p, miR‐141‐3p, miR‐199a‐3p, miR‐205‐5p, and miR‐214‐3p) was measured by RT‐qPCR in formalin‐fixed, paraffin‐embedded tissue samples from 156 MIBC patients who received RC in three urological centers. Samples from 2000 to 2013 were used according to their tissue availability, with follow‐up until June 2016. The patient cohort was randomly divided into a training ( n = 100) and test set ( n = 56). Seventy‐three samples from adjacent normal tissue were used as controls. Kaplan–Meier, univariate and multivariate Cox regression, and decision curve analyses were carried out to assess the association of clinicopathological variables and miRNAs to OS. Both increased (miR‐130b‐3p and miR‐141‐3p) and reduced (miR‐100‐5p, miR‐199a‐3p, and miR‐214‐3p) miRNA expressions were found in MIBC samples in comparison to nonmalignant tissue samples ( P < 0.0001). miR‐199a‐3p and miR‐214‐3p were independent markers of OS in Cox regression models with the significant clinicopathological variables age, tumor status, and lymph node status. The prediction model with the clinicopathological variables was improved by these two miRNAs in both sets. The predictive benefit was confirmed by decision curve analysis. In conclusion, the inclusion of both miRNAs into models based on clinical data for the outcome prediction of MIBC patients after RC could be a valuable approach to improve prognostic accuracy. Abstract : This study demonstrated the usefulness of the microRNAs miR‐199a‐3p and miR‐214‐3p in formalin‐fixed, paraffin‐embedded tissue samples from patients with muscle‐invasive bladder cancer after radical cystectomy as predictive biomarkers of overall survival. In this aspect, the miRNAs combined with traditional clinicopathological factors improved the prediction accuracy for overall survival and could be useful to facilitate clinical decision making for further treatment strategies.